2019
DOI: 10.3389/fendo.2019.00379
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Structural and Functional Diversity of Spexin in Mammalian and Non-mammalian Vertebrate Species

Abstract: Spexin (SPX) is a novel neuropeptide, which was first identified in the human genome using bioinformatics. Since then, orthologs of human SPX have been identified in mammalian and non-mammalian vertebrates. The mature sequence of SPX, NWTPQAMLYLKGAQ, is evolutionally conserved across vertebrate species, with some variations in teleost species where Ala at position 13 is substituted by Thr. In mammals, the gene structure of SPX comprises six exons and five introns, however, variation exists within non-mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 75 publications
0
41
0
Order By: Relevance
“…Spexin has wide tissue distribution patterns in tetrapods and fish, suggesting that spexin has pleiotropic biological consequences in feeding behavior, metabolism, nociception, cardiovascular function, muscle motility, stress, depression, and anxiety (3). The localization of spexins at the cellular level inform these functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spexin has wide tissue distribution patterns in tetrapods and fish, suggesting that spexin has pleiotropic biological consequences in feeding behavior, metabolism, nociception, cardiovascular function, muscle motility, stress, depression, and anxiety (3). The localization of spexins at the cellular level inform these functions.…”
Section: Discussionmentioning
confidence: 99%
“…The fish were bled from the caudal blood vessels into heparinized syringes at 2, 4, 8, and 24 h after injection. Blood was centrifuged (3,200 rpm for 30 min at 4 • C) to obtain plasma samples, which were stored at −20 • C until assayed. This time course is according to standard protocols used previously to test the effect of various hypothalamic neuropeptides on circulating levels of LH and FSH in tilapia (35,36).…”
Section: In Vivo Effect Of Spx1a and Spx1b On Fsh And Lh Releasementioning
confidence: 99%
See 1 more Smart Citation
“…In human, Spexin encoded a prepropeptide of 116 amino acids, which generated a mature peptide undergoing process of posttranslational modifications [ 2 ]. The sequence of mature spexin containing 14 amino acids (NWTPQAMLYLKGAQ) was conserved across vertebrate species [ 3 ]. The gene structure analysis indicated that spexin was closely related to galanin and kisspeptin [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spexin gene or protein had a wide distribution in the central nervous system (CNS) and peripheral tissues in several species, including human, rodents, chicken, anole lizard, and several fish species [ 3 ]. In rat, the spexin protein was observed in stomach fundus, epithelium of small intestine, submucosal layer of esophagus, and hepatocytes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%